2007
DOI: 10.4103/0250-474x.33164
|View full text |Cite
|
Sign up to set email alerts
|

RP-HPLC method for simultaneous estimation of telmisartan and hydrochlorothiazide in tablet dosage form

Abstract: The present work describes a validated reverse phase high performance liquid chromatographic method for simultaneous estimation of telmisartan and hydrochlorothiazide in tablet formulation. Chromatography was performed on a ODS Hypersil C18 (25 cm×4.6 mm I.D) column from thermo in isocratic mode with mobile phase containing acetonitrile:0.05 M KH 2 PO 4 pH 3.0 (60:40). The flow rate was 1.0 ml/min and the eluent was monitored at 271 nm. The selected chromatographic conditions were found to effectively separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…The methods [3][4][5][6][7][8][9][10][11] for telmisartan in combination with other drugs in plasma, serum and in tablets by high-performance liquid chromatography (HPLC) and [12][13][14][15][16][17] for the estimation of hydrochlorothiazide in combination with other drugs in serum and is in tablets by high-performance liquid chromatography (HPLC). A stability indicating LC method has been reported for telmisartan as well as hydrochlorothiazide.…”
Section: Telmisartan a Nonpeptide Molecule Is Chemically 4'-[(14-dmentioning
confidence: 99%
“…The methods [3][4][5][6][7][8][9][10][11] for telmisartan in combination with other drugs in plasma, serum and in tablets by high-performance liquid chromatography (HPLC) and [12][13][14][15][16][17] for the estimation of hydrochlorothiazide in combination with other drugs in serum and is in tablets by high-performance liquid chromatography (HPLC). A stability indicating LC method has been reported for telmisartan as well as hydrochlorothiazide.…”
Section: Telmisartan a Nonpeptide Molecule Is Chemically 4'-[(14-dmentioning
confidence: 99%
“…Individually, TELM is estimated by LC-MS (3), LC-tendem MS (4,5). The majority of methods reported are liquid chromatography in which TELM was estimated simultaneously with hydrochlorthiazide (6,7,8), with ramipril (9, 10), with AmLodipine (11). Some three components are also reported along with TELM such as, Column Switching LC with fluorescence detection (12).…”
Section: Preparation Of Laboratory Mixturementioning
confidence: 99%
“…Simultaneous Quantification of Methadone, Cocaine, Opiates, and Metabolites in Human Placenta by Liquid Chromatography-Mass Spectroscopy has been done [29]. HPTLC method for simultanoeus determination of alprazolam and methyl paraben in tablet dosage form has been carried out by Sagar B. Wankhede et al [30]. Hui Qiao et al have reported a…”
Section: Introductionmentioning
confidence: 99%